Ma(j)e. De la de notación a la apelación. - Sánchez Corrales, Víctor Manuel (2012)
In the present investigation, contextualized within the relationship language-culture-identity, it is analyzed the sociolectal transfer of the Word maje and the amplification of its semantic-pragmatic meaning when used as a nominal form of treatment in the Costa Rican juvenile jargon. Its geographic extension from Mexico to Costa Rica is well defined; however, in a variety of the Costa Rican Spanish, it has acquired the particular feature of a sociolectal marker.